Koroner revaskülarizasyon sonrası kardiyak rehabilitasyonun psikolojik etkileri - Leili Pourafkari; Samad Ghaffari; Jafar Shahamfar; Laleh Tokhmechian; Nader D Nader (KARE Publishing, 2016)
Objective: Prevalence of depression and anxiety increases following cardiac revascularization. The aim of this study was to examine the effects of a cardiac rehabilitation program on psychological status of patients after cardiac revascularization. Methods: A total of 120 patients who underwent either coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) were enrolled in an 8-week rehabilitation program. A brief mood survey was administered before the program and repeated following its completion. Psychological state was assessed for depression, anxiety, panic symptoms, difficulty in adaptation, and relational satisfaction. Changes in mood scores were analyzed with paired t-tests and linear regression models to predict response. Results: A total of 95 men and 25 women were enrolled. Average age was 60.0+-8.4 years. Eighty-two patients underwent PCI, the remaining 38 underwent CABG. Following rehabilitation, depression reduced from 28.3% to 10.8% (p=0.002), anxiety decreased from 21.7% to 9.1% (p=0.012), panic symptoms reduced from 16.7% to 5.8% (p=0.014), and difficulty in adaptation decreased from 30.0% to 10.9% (p=0.0002). Changes in state of depression were not predicted by medical, social, or physical factors, while changes in anxiety were negatively affected by smoking. Psychological changes after rehabilitation were not influenced by presence of acute myocardial infarction (MI) before revascularization. Conclusion: Enrollment in cardiac rehabilitation after coronary revascularization positively impacts psychological status of patients, as assessed by brief mood survey.